Proton pump inhibitors use and the risk of fatty liver disease: A nationwide cohort study. Issue 5 (22nd October 2020) - Pyo, Jeung Hui; Kim, Tae Jun; Lee, Hyuk; Choi, Sung Chul; Cho, Soo‐Jin; Choi, Yoon‐Ho; Min, Yang Won; Min, Byung‐Hoon; Lee, Jun Haeng; Kang, Minwoong; Lee, Yeong Chan; Kim, Jae J
Abstract: Background and Aim: Proton pump inhibitor (PPI)‐induced hypochondria can change the composition of the gut microbiota, inducing overgrowth of small bowel bacteria, which has been suggested to promote the development of fatty liver disease through the gut‐liver axis. In this study, we aimed to investigate the association between PPI use and the risk of fatty liver disease. Methods: A retrospective cohort study was conducted using the Korean National Health Insurance Service‐National Sample Cohort, a nationwide population‐based representative sample, from January 1, 2002, to December 31, 2015. PPI use was identified from treatment claims and considered as a time‐varying variable. Results: During 1 463 556 person‐years of follow‐up, 75 727 patients had at least one PPI prescription, and 3735 patients developed fatty liver disease. The hazard ratio for fatty liver disease comparing PPI users with non‐PPI users was 1.68 (95% confidence interval, 1.61–1.75). When adjusted for multiple confounders, including age, sex, body mass index, smoking, alcohol intake, exercise, income level, and comorbidities, the association was still significant (hazard ratio, 1.50; 95% confidence interval, 1.44–1.57). After considering the amounts of PPIs stratified by cumulative defined daily dose, the dose–response effect was observed until 180 days. Subgroup analysis also revealed that PPI use was correlated to an increased risk of fatty liver disease. Conclusions: This current national wide cohort study suggests that PPI use was associated with an increased risk of fatty liver disease compared with non‐use of PPIs. Clinicians should consider fatty liver as a potential risk when prescribing PPI.